CONTENT MARKETING, DIGITAL INTERACTION, AND UPLOAD FREQUENCY ON CONSUMER PURCHASING DECISIONS IN DIGITAL MARKETING THROUGH INSTAGRAM SOCIAL MEDIA - Zalwa Raniah Salshabilla; Mochamad Rizal Yulianto (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the influence of Content Marketing, digital interaction, and upload frequency on consumer purchasing decisions on Instagram. Method: The research method used a quantitative approach with a purposive sampling technique on 100 respondents, as well as multiple linear regression analysis using SPSS 25. Results: The results showed that marketing content had a positive but insignificant effect, while digital interaction and upload frequency had a significant positive effect on purchasing decisions. Simultaneously, all three variable had a significant effect with a contribution of 56,2%. Novelty: This finding emphasizes the importance of integrating content, interaction, and upload consistency to improve consumer purchasing decisions on Instagram.